2014
DOI: 10.4012/dmj.2014-002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sandblasting on surface roughness of zirconia-based ceramics and shear bond strength of veneering porcelain

Abstract: This study aims to investigate the effect of sandblasting on the surface roughness of zirconia and the shear bond strength of the veneering porcelain. Pre-sintered zirconia plates were prepared and divided into four groups. Group A were not treated at all; group B were first sandblasted under 0.2 MPa pressure and then densely sintered; group C and D were sintered first, and then sandblasted under 0.2 MPa and 0.4 MPa pressures respectively. Surface roughness was measured and 3D roughness was reconstructed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 40 publications
(47 reference statements)
5
79
0
1
Order By: Relevance
“…Recently, different modification methods of pre-sintered zirconia for the improvement of bonding were reported in in vitro studies [9,36,37]. Sandblasting prior to zirconia sintering increased the surface roughness and bond strength to veneering ceramics compared with that after sintering [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, different modification methods of pre-sintered zirconia for the improvement of bonding were reported in in vitro studies [9,36,37]. Sandblasting prior to zirconia sintering increased the surface roughness and bond strength to veneering ceramics compared with that after sintering [9].…”
Section: Discussionmentioning
confidence: 99%
“…For achieving long-term clinical success, various approaches have attempted the improvement of the bonding between zirconia and either veneering ceramics or cement materials [8,9,10,11,12,13]. Modification of the zirconia framework and sandblasting (airborne abrasion) of zirconia surfaces have been recommended to improve the fracture resistance of veneering ceramics [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that sandblasting of zirconia before sintering is a useful method to increase surface roughness. 34 Conversely, Moon et al 35 reported that there was no significant difference in surface roughness between the groups abraded before and after sintering. The aim of the present study was to investigate the effect of APA on presintered zirconia on surface roughness, zirconia grain size, t-m phase transformation, and the effect of these parameters on the bond strength of zirconia to resin cement.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies regarding zirconia surface modifications to enhance osseointegration, involving machining 13) , sandblasting 14,15) , laser treatment 16) , plasma spraying 17) , sol-gel 18) and surface bioactive coatings [19][20][21] . However, surface modification of zirconia ceramics is technically difficult 22) due to its high hardness.…”
Section: Introductionmentioning
confidence: 99%